Trauma-associated bleeding: management of massive transfusion. Issue 2 (April 2016) - Stephens, Christopher T.; Gumbert, Sam; Holcomb, John B.
Abstract : Purpose of review: Early treatment goals in the bleeding trauma patient have changed based on recent research findings. Trauma patients requiring a massive transfusion protocol have shown a decreased mortality based on a more aggressive and balanced approach to blood product resuscitation. This chapter will review the recent advances in managing the bleeding trauma patient. Recent findings: Recent data have suggested a combined approach of early ratio-based blood product use, bedside viscoelastic hemostatic assays, hemostatic resuscitation, and finally goal-directed therapy to complete resuscitation. Summary: There is now evidence to support the early use of a 1 : 1 : 1 blood product transfusion protocol to restore lost circulating volume, improve oxygen carrying capacity, replace diluted platelets, and replenish clotting factors in massively bleeding trauma patients. Further study is needed to determine whether prehospital initiation of blood products and pharmacological adjuncts will improve outcomes.